Meningkatkan Kemampuan Mind Mapping Siswa Dalam Pembelajaran Tari Dengan Menggunakan Aplikasi Canva - Millanie Yuliaramsyah; Agus Budiman; Agus Supriyatna (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Learning in the 21st century must be able to produce young people to face the growth or development of information and communication technology in social life. This research is motivated by the low intelligence of high school students in learning dance, especially in the problem of ability to map the subject matter provided by the teacher. The purpose of this study is to improve students' knowledge intelligence in remembering and memorizing dance subject matter delivered by the teacher by applying the canva application. This study uses the action research method by conducting three main stages, namely: before action, learning action and after learning action. Research data was obtained through a questionnaire instrument with google form in seeing the level of student understanding when mapping the subject matter using the canva application. In addition, research data was also obtained through interviews with students. The results showed that using the canva application media in dance learning can improve students' ability to remember dance subject matter given by the teacher. Students can map the teaching material provided by the teacher through the canva application made by the students themselves. They grouped each sub-material discussed and given by the teacher at each meeting. Action learning activities in five stages of learning. Learning results using media show better because it does not cause boredom for students in receiving and understanding the material delivered by the teacher.